Kualitas Visum et Repertum Perlukaan di RSUD Indrasari Kabupaten Indragiri Hulu Periode 1 Januari 2009-31 Desember 2013 - Dedi Afandi; Tuti Restuastuti; Winda Kristanti (Jurnal Ilmu Kedokteran, 2015)
Visum et Repertum (VeR) of injury is the most case that requested by the investigator to emergency physician.Because VeR gives the important role in the judicial process in criminal offense cases, so that the good quality VeR isrequired. This study was aimed to know the quality VeR of injury in Indrasari General Hospital Indragiri Huluregency during 1 January 2009-31 December 2013. This study used descriptive retrospective aproach. This studyused Herkutanto’s score to evaluate 13 subtances in VeR. The sample of this study was all data of VeR of injury inIndrasari General Hospital Indragiri Hulu regency during 1January 2009 -31 December 2013 and the total data inIndrasari Hospital was 137 data. This study suggested that the highest living injury victim are living in the age group22 - 40 years amount 73 VeR (53.28%). The most injury case to the male as much as 92 VeR (67.153%). The highesttype of violence is blunt violent as much as 109 VeR and the most in 22-40 ages group. The VeR quality preliminarypart is 69.34% (medium), the reporting part is 37.83% (poor) and the conclusion part is 49.45% (poor). Based fromthat data, the conclusion of the quality of VeR indrasari hospital is poor (46.82%).